Perspectives in Academic Writing: Insights from English Education Students in Islamic Higher Education Institutions - khawa, dewi; Zumala Dwi Andriani , Zulfi (Darussalam English Journal (DEJ), 2024)
This study explores the perspectives of students in Islamic higher education institutions on academic writing, focusing on English Education programs at Institut Agama Islam Darussalam Blokagung Banyuwangi (IAIDA) and Universitas Nurul Jadid Probolinggo (UNUJA). Using a qualitative approach, data were gathered through in-depth interviews with sixty senior students. The findings highlight the critical importance of English proficiency for academic success, though students face challenges with grammar, sentence structure, and vocabulary. AI tools like Google Translate and Grammarly are widely used to aid writing, though they fall short in generating original content. Writing and research methodology courses are deemed essential, but students call for more effective instruction and supervision. The need for clear, consistent academic writing regulations is emphasized, as current ambiguities hinder adherence to standards. Students view academic writing as crucial for both academic completion and career preparation, underscoring the broader educational significance of writing skills. The study concludes that enhanced support and targeted interventions are necessary to improve academic writing proficiency and critical thinking among students in these institutions.